Unilateral multiple facial angiofibromas: A case report with brief review of literature - Rameshwar Gutte; Uday Khopkar (Wolters Kluwer Medknow Publications, 2013)
Tuberous sclerosis (TSC) is an autosomal dominant hereditary condition with many varied forms of clinical presentation. The most frequent cutaneous findings in TSC include multiple angiofibromas, hypopigmented macules, periungual fibromas, and shagreen patch. Rarely, unilateral multiple facial angiofibromas have been reported. We report a case of unilateral multiple facial angiofibromas without any other manifestations of TSC. Although rare, unilateral multiple facial angiofibromas may be a mosaic form of TSC.